The Development of The English Language Learning Videos Through Role Playing Based on Personalization Through A Data Driven Approach for Deaf Students - Purnomo, Listiya Ike; Fitriyah, Fitriyah; Friska, Yuliana; Husnul, Nisak Ruwah Ibnatur (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to produce English language learning videos through role-playing based on personalization through a data-driven approach for deaf students. This research method used research and development with the ADDIE model, namely analysis, design, development, implementation, and evaluation. The subjects in this study were 2 material experts, 2 learning video media experts, 2 practitioners, and 20 student responses. The results showed that the English language learning video through role-playing based on personalization through a data-driven approach had been tested for validity and reliability, so it is feasible to use in the learning process. The implementation results of this innovation on 3 deaf students obtained scores above 80. This research implies that deaf students find it easier to understand English language material, especially prepositions, comparisons, and subject-verb agreement.